The ‘Good’ and ‘Bad’ Refugees? Imagined Refugeehood(s) in the Media Coverage of the Migration Crisis - Marta SZCZEPANIK (Journal of Identity and Migration Studies, 2016)
This text is an attempt to analyze a particular, normative aspect of the media narrative about refugees during the recent migration crisis in Europe. It looks at the substantive semantic distance between the ‘good’ or ‘real’ refugees presented in some media outlets and the definition of a refugee under international law. This difference is later explained by a particular kind of exposure to the events of the refugee crisis – a ‘mediated experience’, and by the existence of a normative ‘refugee archetype’. I look at images representing refugees through the lenses of John B. Thompson’s (1995) concept of opposition between lived and mediated experience – the figures of ‘bad’ and ‘good’ refugees are seen as belonging to the order of mediated experience, therefore, as argued by Thomson, impersonal and dispersed in time and space. Finally, I refer to the Malkki’s (1996) concept of a refugee as a ‘universal humanitarian subject’ – an apolitical and de-historicized figure, reduced to the role of aid beneficiary which serves me to explain the ambiguity of representations of refugees and their dependence on political interests.